2017
DOI: 10.1016/j.juro.2016.09.117
|View full text |Cite
|
Sign up to set email alerts
|

Multisite Experience of the Safety, Detection Rate and Diagnostic Performance of Fluciclovine ( 18 F) Positron Emission Tomography/Computerized Tomography Imaging in the Staging of Biochemically Recurrent Prostate Cancer

Abstract: Purpose Sensitive detection of cancer foci in men experiencing biochemical recurrence following initial treatment of prostate cancer is of great clinical significance with a possible impact on subsequent treatment choice. We describe a multisite experience of the efficacy and safety of the positron emission tomography/computerized tomography agent fluciclovine (18F) after biochemical recurrence. Materials and Methods A total of 596 patients underwent fluciclovine (18F) positron emission tomography/computeriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
117
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 167 publications
(129 citation statements)
references
References 26 publications
7
117
2
3
Order By: Relevance
“…Regarding the PET/CT tracers comparative studies between prostate-specific membrane antigen (PSMA) and choline have demonstrated superiority of PSMA to identify bone lesions [98]. The PET tracer 18 Ffluciclovine has recently been approved for use in North America; available data indicate good detection rates both for lymph nodes and for bone disease in biochemical recurrence of prostate cancer [99]. The diagnostic performance of fluciclovine PET was found to be superior to CT and to choline PET but there are no comparative data versus WB-MRI and PSMA PET [100].…”
Section: Bone Disease Assessments In Apcmentioning
confidence: 99%
“…Regarding the PET/CT tracers comparative studies between prostate-specific membrane antigen (PSMA) and choline have demonstrated superiority of PSMA to identify bone lesions [98]. The PET tracer 18 Ffluciclovine has recently been approved for use in North America; available data indicate good detection rates both for lymph nodes and for bone disease in biochemical recurrence of prostate cancer [99]. The diagnostic performance of fluciclovine PET was found to be superior to CT and to choline PET but there are no comparative data versus WB-MRI and PSMA PET [100].…”
Section: Bone Disease Assessments In Apcmentioning
confidence: 99%
“…Several molecular imaging approaches have been proposed over the last decade. The best results for assessing patients with PCa recurrence were obtained with 18 F-fluciclovine and PSMA-targeted PET radiotracers (2)(3)(4)(5).…”
mentioning
confidence: 99%
“…However, the DR in the lowest serum PSA quartile (≤0.79 ng/mL) was as low as 41.4% . In a prospective comparison with 11 C‐choline in 89 patients, 18 F‐fluciclovine resulted in being slightly superior in terms of sensitivity and superior in terms of specificity. In particular, the 11 C‐choline and 18 F‐FACBC, sensitivities were 32% and 37%, the specificities 40% and 67%, the accuracies 32% and 38%, the PPVs 90% and 97%, and the NPVs 3% and 4%, respectively …”
Section: Evidence Acquisitionmentioning
confidence: 55%